The Limitations of the Role of Majelis Ta’lim in Resolving Conflicts Regarding Husbands' Maintenance for Wives in the City of Cilegon - Irfan Amin Sam; Wazin; Itang; Sayehu; Syihabudin (Bulletin of Community Engagement, 2026)
This article examines why Majelis Ta’lim has not yet functioned effectively as a forum for resolving disputes concerning a husband’s obligation to provide maintenance in Cilegon City. The study begins by addressing the persistent gap between the recognition of maintenance rights in Islamic family law and Indonesian positive law and the continued vulnerability of wives when such rights are neglected in everyday marital life. Employing a descriptive qualitative field research approach, the study finds that Majelis Ta’lim primarily serves as an initial complaint forum due to its social trust, emotional closeness, and moral authority within the community. Nevertheless, its practical contribution remains limited. The main obstacles include the predominance of female congregants, the limited integration of fiqh teachings with legal literacy, and the absence of continuous assistance and referral mechanisms to formal legal institutions. Therefore, this article argues that strengthening the role of Majelis Ta’lim requires moving beyond spiritual reinforcement toward the development of community-based mediation and legal literacy programs that can more effectively support and protect wives’ financial rights